(untitled) (Docentes 2.0 Journal, 2025)
Autism Spectrum Disorder (ASD) is considered a neurodevelopmental condition that affects brain abilities and negatively influences communication, social interaction, and behavior. This study aimed to identify the needs that must be addressed regarding the inclusion of children with Autism Spectrum Disorder (ASD) in classrooms belonging to the Jacinto Gordillo Educational Unit, located on Isabela Island. Research was conducted within the interpretive paradigm, under the case study method with a qualitative approach, descriptive phenomenological design, and cross-sectional, in which the participant observation form instrument was used, which allowed the analysis of the barriers detected in the pedagogical, communication, emotional, social, and environmental categories, with effects on educational inclusion. As a result, the observation sheet revealed that inclusive practices were indeed being developed within the institution, including curricular adaptations, partial implementation of Universal Design for Learning (UDL), and adjustments to the infrastructure. However, deficiencies were detected in verbal and nonverbal communication, emotional management, and the development of autonomy. It is concluded that the implementation of the proposed teaching strategy must be supported by specialized training, teaching resources, and an ongoing evaluation system that promotes an inclusive institutional culture based on respect and participation of all stakeholders.